Nation dance religion, identity, and cultural difference in the Caribbean - Taylor, Patrick (Bloomington Indiana University Press, 2001)
Across the waters /Eva Fernandez Bravo [and others] --How shall we sing the Lord's song in a strange land? /Althea Prince --Communicating with our gods /Petronella Breinburg --Intersemiotics of Obeah and Kali Mai in Guyana /Frederick Ivor Case --Religions of African origin in Cuba /Maria Margarita Castro Flores --Sheba's song /Patrick Taylor --Themes from the West Indian church history in colonial and post-colonial times /Arthur C. Dayfoot --Congregationalism and the Afro-Guianese autonomy /Juanita De Barros --Eden after Eve /Judith Soares --Current evolution of relations between religion and politics in Haiti /Laënnec Hurbon --Jamaican diasporic identity /Barry Chevannes --Identity, personhood, and religion in Caribbean context /Abrahim H. Khan --Sanfancón /Frank F. Scherer --Diasporic mo(ve)ment /Sean Lokaisingh-Meighoo.
Dealing with the ongoing interaction of rich and diverse cultural traditions from Cuba and Jamaica to Guyana and Surinam, Nation Dance addresses some of the major contemporary issues in the study of Caribbean religion and identity. The book's three sections move from a focus on spirituality and healing, to theology in social and political context, and on to questions of identity and diaspora
Diasporic mo(ve)ment Sean Lokaisingh-Meighoo.
Includes bibliographical references and index. - Description based on print version record
Online-Ausg.
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Religion and culture -- Caribbean Area; Ethnicity -- Caribbean Area; Religion et culture -- Carai͏̈bes (Région); Ethnicité -- Carai͏̈bes (Région); Ethnicity -- Caribbean Area; Religion and culture -- Caribbean Area; TRAVEL ; Special Interest ; Religious; Ethnicity; Religion; Religion and culture; Godsdienst; Culturele identiteit; Religion ; History; Caribbean Area -- Religion -- Caribbean Area; Carai͏̈bes (Région) -- Religion; Caribbean Area -- Religion; Caribbean Area; Caribisch gebied; Electronic books